EMPATHY AND ITS IMPORTANCE IN THE WORK OF GUIDES (International Conference on Educational Discoveries and Humanities, 2025)
Empathy is a key skill in professional guiding, shaping communication, leadership, and the overall tourist experience. This article examines both theoretical and practical ways to develop empathy in the tourism industry. Based on emotional intelligence and experiential learning theories, it shows that empathy can be taught through reflective and interactive training. Methods such as role-playing, mindfulness, and intercultural communication help guides understand emotions and respond with sensitivity. The paper also discusses the role of organizations and leadership in promoting an empathetic culture. Ultimately, empathy turns guiding from simple information delivery into meaningful human interaction that builds trust, respect, and cultural understanding among people from diverse backgrounds.